SOCIAL AND PEDAGOGICAL ENVIRONMENT TRAINING AND PROFESSIONAL STUDIES AS A FACTOR OF FORMATION OF INNOVATIVE POTENTIAL FUTURE SOCIAL WORKERS - Savelchuk, Irina B. (Educological discourse, 2015)
The article deals with the creation, content and use of social and educational environment of educational and professional studies of higher education institutions which train social workers. Characterized on the basic principles of the establishment and operation of student teaching and professional studies. Reveals the influence of environment on the formation of innovative potential students through the processes of self-regulation, self-realization, self-presentation, self-actualization contributing to its development and activation.